Mucosa of murine detrusor impairs β2‐adrenoceptor‐mediated relaxation. Issue 6 (12th May 2014) - Propping, Stefan; Newe, Manja; Kaumann, Alberto J.; Wirth, Manfred P.; Ravens, Ursula
<x xml:space="preserve">Abstract</x> Aims To investigate the role of the mucosa in (−)‐isoprenaline‐induced relaxation of mouse detrusor muscle and to characterize the β‐adrenoceptor subtypes involved. Methods Isolated intact and mucosa‐denuded muscle strips from the urinary bladder of male C57BL6 mice were pre‐contracted with KCl (40 mM) and were relaxed with increasing concentrations of the β‐adrenoceptor (β‐AR) agonist (−)‐isoprenaline and forskolin in the presence and absence of the subtype‐selective β‐AR blockers CGP20712A (β1‐ARs), ICI118, 551 (β2‐ARs), and L748, 337 (β3‐ARs). Results Force development in response to KCl was larger in mucosa‐denuded than in intact preparations and was almost completely relaxed with increasing concentrations of (−)‐isoprenaline. Mucosa‐denuded muscles were about 10‐fold more sensitive to (−)‐isoprenaline than intact muscles. CGP20712A did not affect the concentration–response curves (CRCs) to (−)‐isoprenaline, ICI118, 551 shifted the CRC further to the right in denuded than in intact strips so that the difference between them was abolished. Combined exposure to β1‐AR and β2‐AR blocker yielded the same result. L748, 337 did not significantly affect the CRC to (−)‐isoprenaline but caused additional blockade to ICI118, 551 in the presence of intact mucosa. Conclusions The mucosa of mouse detrusor strips impairs KCl‐induced force development and reduces the sensitivity to β‐AR‐induced relaxation. The relaxing response to (−)‐isoprenaline as well as the mucosa effect thereupon are mainly mediated by β2‐ARs. A minor involvement of β3‐ARs becomes apparent particularly at high (−)‐isoprenaline concentrations. Neurourol. Urodynam. 34:592–597, 2015. © 2014 Wiley Periodicals, Inc.